A Bibliometric Analysis: Remote Sensing Literature in Dimensions.ai Database - Azhari, Septian Cahya; Iman Hilman; Siti Fadjarajani; Guruh Sukmo (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
This research using bibliometric analysis aims to identify and visualize research developments in the field of remote sensing studies. The data is obtained from 2021-2022 through dimensions.ai with criteria for articles that have a digital object identifier (DOI). The data generated were 2645 articles which were then analyzed using the VosViewer device. The data analyzed includes the development of popular keywords, affiliations, countries and authors who do a lot of research in the field of remote sensing. The results of the study found 4 clusters with 216 items for keywords, 6 clusters and 36 items for authors, 15 clusters and 323 items for affiliation, 7 clusters and 61 items for country analysis which mostly conducted research on remote sensing.